O EXERCÍCIO DA CIDADANIA REPRODUTIVA OBSTADO PELA IRREFLEXÃO E PELA BALANIDADE DO MAL, DO PENSAMENTO DE HANNAH ARENDT (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The aim of this article is to analyze the exercise of reproductive citizenship based on Hannah Arendt's concept of thoughtlessness and the consequent banality of evil. In fact, it is intended, through this study, to make a comparison between Arendtian observations on the irrational way of simply obeying orders and following a predetermined code of ethics, without reflecting on the conduct taken, leading to the banality of poorly described by the philosopher at the time of Eichmann's judgment, with the medical practices that make artificial reproduction, at any cost, mowing the reproductive citizenship from those who are involved in the act.